Evaluation and mechanism of the antioxidant activity of lactic acid bacteria - Xiao, Yuyang; Yang, Jian; Zhang, Xupeng; Yang, Meng; Qin, Yuexiang; Huang, Pinfang; Liu, Dan (Folia microbiologica, 2025)
Lactic acid bacteria (LABs) have emerged as a significant area of study within the field of probiotics due to their diverse health benefits and wide application. This review examines the various methods used to evaluate the antioxidant activity of LABs, including in vitro chemical evaluation methods, cell model evaluation methods, and in vivo evaluation methods. Comprehensive overview of the various assessment techniques employed to elucidate the multifaceted roles of LABs in enhancing the body's natural defenses against oxidative damage. Moreover, this review emphasizes several pivotal aspects of the antioxidant effects of LABs, including the activation of the antioxidant signal pathway, the induction of antioxidative enzymes, the formation of a ROS-binding system, the production of metabolites, the enhancement of intestinal barrier integrity, the activation of the oxidative damage repair system, and the assurance of mitochondrial function. These represent the key antioxidant effects of LABs. The synthesis of this information advances our understanding of the dynamic and diverse antioxidant effects of LABs, providing a foundation for further research into their therapeutic applications in combating oxidative stress-related disorders. Future research should employ multi-omics technologies, genetic engineering, studies on synergistic effects, and large-scale clinical trials to further elucidate the molecular mechanisms underlying the antioxidant effects of LABs. This will promote their application in functional foods, pharmaceuticals, and cosmetics, providing a scientific basis for the development of more efficient antioxidant products.
Keywords: Regulation mechanism; Antioxidant activity; Lactic acid bacteria; Evaluation system